2009
DOI: 10.2134/jeq2008.0526
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Constructed Wetland for the Detention of Agricultural Runoff for Water Quality Improvement

Abstract: The goal of this study was to construct a wetland that would detain runoff from a 162-ha watershed for the purposes of improving water quality. The volume of runoff that needed to be detained was determined to be that amount coming off the 162-ha watershed consisting of 146 ha of cultivated crop land and 16 ha of pasture that exceeded the amount that would have come off of the watershed in its natural, forested state. The Soil Conservation Service (now the Natural Resource Conservation Service [NRCS]) runoff c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
0
10
0
2
Order By: Relevance
“…In the UK, the value of wetland recreation is recognised (Braskerud et al ., 2005; Deasy et al ., 2009), with recommendations for wetland creation across 2% of catchments having being made (Millhollon et al ., 2009). Others have suggested smaller, strategically placed features could play a key role (Braskerud et al ., 2005; Ockenden et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, the value of wetland recreation is recognised (Braskerud et al ., 2005; Deasy et al ., 2009), with recommendations for wetland creation across 2% of catchments having being made (Millhollon et al ., 2009). Others have suggested smaller, strategically placed features could play a key role (Braskerud et al ., 2005; Ockenden et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have demonstrated that various macrophytes are effective in treating polluted water, including municipal waste water (Ge´rard, Jean-Luc, and Thierry 2002;Jing et al 2002), agricultural non-point source pollution (Headley, Huett, and Davison 2001;Millhollon et al 2009), and eutrophic water bodies (Green and Upton 1994). Macrophytes can take up nitrogen and phosphorus from surface water (Tanner 2001;Wang et al 2007), filter suspended particulate organic matter, increase the oxygen concentration of the water, and reduce flow velocity, which increases the water residence time.…”
Section: Nitrogen and Phosphorus Removal And Morphological And Physiomentioning
confidence: 99%
“…[13][14][15][16][17] Although constructed wetlands are recognised as reliable technology for wastewater treatment, [18,19] the technology has only recently begun to be widely implemented for mitigation of non-point source pollution such as agricultural run-off. [10,11,15,17,20] Previous research has addressed the use of vegetated free water surface constructed wetlands to remove nutrients of various types including N [6,12,17,21] and P. [11,15,17,[21][22][23] In addition, other research has focused on the use of free water surface constructed wetlands to remove pesticides of various types including herbicides and insecticides either singly or in mixtures. [10,13,16,24] However, more complex mixtures of nutrients and pesticides in combination, as well as comparisons between nutrient only and pesticide only conditions have been less well studied.…”
Section: Introductionmentioning
confidence: 99%